Performance comparison on biomass gasification reactor for hydrogen production - Muhammad Bilal, Muslim; Suriyati, Saleh; Tuan Amran, Tuan Abdullah; Arshad, Ahmad; Noor Asma Fazli, Abdul Samad (2016)
Nowadays biomass becomes one of the most important sources of renewable energy due to its abundant reserves and relatively low price compared with other energy sources. The main advantage of biomass as renewable energy source is its capability to produce near zero carbon dioxide emissions through the use of gasification process. Usually the gasification process either using downdraft fixed bed or bubbling fluidized bed is the most preferred gasifier in order to produce the hydrogen gas which is useful for energy production. In order to represent this gasification process, Aspen Plus simulator can be used as a process simulation study. However most of the simulation work done by the researchers are focusing on the coal gasification and only a limited work done on the biomass gasification. In addition, different gasifiers are used for different biomass which make its selection and use become confusing. Therefore, the objective of this study is to evaluate and compare the gasifier performance between bubbling fluidized bed and downdraft fixed bed gasifiers using oil palm frond (OPF) as biomass input for hydrogen production. For this purpose, a comprehensive process model including hydrodynamics and reaction kinetics for both gasifiers are developed in the Aspen Plus software. The performance analysis for the biomass is evaluated in terms of the total of the syngas produced particularly hydrogen gas. Furthermore, the impact of operating variables such as air to biomass ratio and gasifier temperature on the syngas production are investigated through sensitivity analysis. Based on the performances and sensitivity analysis, gasification using fluidized bed produces 7.5% of hydrogen gas at operating temperature of 740°C and air to biomass ratio of 0.01 compared to only 5.4% of hydrogen gas at temperature of 760°C for fixed bed reactor.